Preparation and Synergistic Anti-Tumor Effect of Iridium Oxide Nanocomposites under Microscope - Xudong He; Feng Xiang; Zhangyi Xu (International Journal of Analytical Chemistry)
In order to solve the great difficulties in cancer prevention, diagnosis, and treatment, a preparation method of iridium oxide nanocomposites under the microscope was proposed in this paper. Through a retrospective analysis of an experiment, IrOx nanoparticles were prepared by direct hydrothermal hydrolysis and loaded with chemotherapy drug adriamycin to construct nanodrug-loaded complex IrOx@DOX. At the same time, IrOx, as a sound-sensitive agent, can produce ROS under US irradiation, amplify intracellular oxidative stress, accelerate tumor cell death, and finally achieve the effect of SDT chemotherapy synergistic therapy. The experimental results show that IrOx@DOX has the dual response of pH and US, and the inhibition rates are 27%, 57%, and 76%, respectively. At the same time, ultrasound not only can enhance the uptake of nanoparticles by cells but also can promote the release of DOX in cells, which provides a basis for subsequent SDT chemotherapy synergistic therapy. Conclusion. Iridium oxide nanocomposite DOX combined with SDT can obtain a good therapeutic effect, which has positive feedback on the efficacy of chemotherapy and the therapeutic effect of cancer surgery.